2018
DOI: 10.1161/strokeaha.117.018889
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Poststroke Neurocognitive Disorders Using National Institute of Neurological Disorders and Stroke-Canadian Stroke Network, VASCOG Criteria (Vascular Behavioral and Cognitive Disorders), and Optimized Criteria of Cognitive Deficit

Abstract: URL: https://www.clinicaltrials.gov. Unique identifier: NCT01339195.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 51 publications
3
46
0
3
Order By: Relevance
“…On a group level, we found severe impairment in almost every cognitive domain. This corresponds with findings of other recent studies; however, contrary to those studies, we found memory to be the most severely impaired of the cognitive domains (12,17). This finding continued to be significant when patients with pre-stroke dementia were excluded.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On a group level, we found severe impairment in almost every cognitive domain. This corresponds with findings of other recent studies; however, contrary to those studies, we found memory to be the most severely impaired of the cognitive domains (12,17). This finding continued to be significant when patients with pre-stroke dementia were excluded.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have reported conflicting results regarding the prognosis for patients suffering PSCI; these have indicated deterioration, no progression, and even improvement in cognition over time for subgroups ( 4 11 ). Several cognitive domains are affected in PSCI; of these, impairment in attention and executive function seem to be the most prevalent and severe shortly after and a long time after suffering a stroke ( 12 16 ). A recent study on PSCI a short time after a stroke showed a high prevalence of impairment in global cognition and in the five most commonly assessed domains: attention, memory, language, perceptual-motor function, and executive function ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the VASCOG criteria, harmonization of the threshold used to determine cognitive impairment will be an important point considering its major influence on the diagnosis of cognitive deficit. The recent finding that the 5th percentile threshold applied to a global cognitive score provides the highest sensitivity and specificity among various deficit criteria [51] may contribute to this objective.…”
Section: Discussionmentioning
confidence: 99%
“…Somatosensory and cognitive impairment, cardiorespiratory disability following stroke, are associated with reduced activity partic-ipation. [18][19][20] Winovich et al observed that markers of physical function-walking speed and grip strength-were consistently associated with survival and recovery after ischemic stroke. 21 Leijon et al showed that the symptoms and signs indicate that the crucial factor for the development of CPSP is a lesion affecting the spino-thalamo-cortical pathway important for temperature and pain sensibility.…”
Section: Discussionmentioning
confidence: 99%